Preparation of N-TiO2 Using a Microwave/Sol-Gel Method and Its Photocatalytic Activity for Bisphenol A under Visible-Light and Sunlight Irradiation. (20th February 2013) - Wu, Chung-Hsin; Kuo, Chao-Yin; Lin, Chin-Jung; Chiu, Peng-Ke
Abstract : This study applied the microwave/sol-gel method to prepare nitrogen-doped TiO2 (N-TiO2 ). The N-TiO2 was immobilized in glass balls to form N-TiO2 /glass beads and applied to degrade Bisphenol A (BPA) under visible-light and sunlight irradiation. The characteristics of the prepared photocatalysts were analyzed by X-ray diffraction (XRD), UV-Vis spectroscopy, Fourier transform infrared spectroscopy (FTIR), and X-ray photoelectron spectroscopy (XPS). Experimental results demonstrate that the percentage of anatase increased as the amount of N in N-TiO2 increased. Compared with the undoped TiO2 (420 nm), spectra show that the absorption edge shifted to a longer wavelength (445 nm) after N doping. The XPS characterization confirms the substitution of crystal lattice O to N species in N-TiO2, forming Ti–O–N and N–Ti–O. With an increased N/Ti ratio, photodegradation efficiency increased and then decreased; moreover, the optimal amount for N doping was determined as an N/Ti mole ratio of 0.08 (0.1 NT). The efficiency of 0.1 NT in doing BPA photodegradation was greater than that of Degussa P25. After reaction for 61 min, the mineralization percentage of 0.1 NT under visible-light irradiation reached 41%. Photocatalyst efficiency decreased as the number of repeats increased in the visible-light/N-TiO2 system; however, these systems were stable during reaction.